Water efficiency in the construction of the Academic Unit of Cabo de Santo Agostinho of the Federal Rural University of Pernambuco (Research, Society and Development, 2022)
Cabo de Santo Agostinho is located in an area of ​​extensive rainfall, which makes the Academic Unit of the Federal Rural University of Pernambuco capable of achieving its water efficiency through the use of rainwater. This work aims to evaluate the water efficiency by the reception and reuse of rainwater in the unit. A survey of rainfall data was carried out in the municipality of Cabo from years 1987 to 2017 with the historical base of the Pernambuco Water and Climate Agency and the analysis of the precipitation data series used the ClimAp 3.0 software. The water consumption during the unit's operation was obtained by consulting the descriptive memorial of the building, followed by the calculation of the consumption estimate through the characterization of the sanitary appliances with the manufacturers. The roof projections identified in the blueprint plan were used to calculate the covered areas of the building. Precipitation in the municipality was considered high, with an average of 1,863.4 mm during the evaluated interval. The consumption of flushes is 63.15% of the unit's total water consumption. The amount of green area observed causes the consumption of non-potable water to exceed availability, requiring the use of potable water for the driest months. Total water efficiency for non-potable water and its legal applications was achieved throughout the year, even on less rainy days, confirming that rainwater harvesting and storage conditions are essential for water efficiency in buildings.